Effects of chronic deoxynivalenol exposure on p53 heterozygous and p53 homozygous mice. (October 2016) - Bondy, G.S.; Coady, L.; Curran, I.; Caldwell, D.; Armstrong, C.; Aziz, S.A.; Nunnikhoven, A.; Gannon, A.M.; Liston, V.; Shenton, J.; Mehta, R.
Abstract: Deoxynivalenol (DON) is a secondary metabolite associated with Fusarium species pathogenic to important food crops. A two-year feeding study reported that DON was non-carcinogenic in B6C3F1 mice. The present study was conducted to further characterize the chronic effects of DON by exposing cancer-prone transgenic p53 heterozygous (p53+/−) male mice and p53 homozygous (p53+/+) male mice to 0, 1, 5, or 10 mg DON/kg in diet for 26 weeks. Gross and microscopic organ-specific neoplastic and non-neoplastic changes and expression profiles of key hepatic and renal genes were assessed. Few toxicologic differences between p53+/+ and p53+/− mice were observed, and no tumours were observed due to DON. The results indicated that DON was non-carcinogenic and that reduced expression of the p53 gene did not play a key role in responses to DON toxicity. The lack of inflammatory and proliferative lesions in mice may be attributed to the anorectic effects of DON, which resulted in dose-dependent reductions in body weight in p53+/+ and p53+/− mice. Hepatic and renal gene expression analyses confirmed that chronic exposure to DON was noninflammatory. The effects of 26-week DON exposure on p53+/+ and p53+/−mice were consistent with those previously seen in B6C3F1 mice exposed to DON for two years. Highlights: Deoxynivalenol did not produce tumours in cancer-prone p53+/− mice. Deoxynivalenol caused feed refusal and reduced body weight gain in mice. Deoxynivalenol induced gene expression changes indicative of anti-inflammatory and anti-proliferative responses in mice.